Tuning structural characteristics of red mud by simple treatments. Issue 15 (15th November 2016) - Kurtoğlu, Samira Fatma; Soyer-Uzun, Sezen; Uzun, Alper
Abstract: Red mud (RM) is a hazardous waste produced vastly by aluminum industry worldwide. Because of its rich metal oxide content, it has potential to be utilized in various applications, such as ceramics production, construction, and catalysis. Here, we investigated the structural modification of RM by simple acid treatments using HCl and H2 SO4 at different molarities, and at different digestion temperatures followed by calcinations at various temperatures. Structures before and after these treatments were characterized in deep detail by combining electron microscopy, diffraction, and spectroscopy complemented by thermal analysis and mass spectrometry to elucidate any changes in morphology, structure, and chemical composition introduced by these treatments. Results showed that acid treatments tremendously affect chemical composition; for instance, amount of Fe2 O3 changes from 37 to 46 wt%, while that of minor components, such as Na2 O, varies from approximately 9 wt% to trace amounts. Moreover, data also illustrated that high acid digestion temperature (220 °C) leads to significant improvements in surface area, from 17 m 2 /g to values exceeding 200 m 2 /g. Results presented here provide a guideline for modifying RM by simple treatments to tune its structural characteristics, potentially offering opportunities for its utilization as cost effective and environmentally friendly solutions to various applications.